A comparative study of four types of free flaps from the ipsilateral extremity for finger reconstruction. - Yujie Liu (Public Library of Science (PLoS), 2014)
Aim To compare the outcomes of finger reconstruction using arterialized venous flap (AVF), superficial palmar branch of the radial artery (SPBRA) flap, posterior interosseous perforator flap (PIPF), and ulnar artery perforator free (UAPF) flap harvested from the ipsilateral extremity. Methods We retrospectively reviewed the outcomes for 41 free flaps from the ipsilateral extremity in the reconstruction of finger defects in 41 patients with small/moderate skin defects, including 11 AVFs, 10 SPBRA flaps, 10 PIPFs, and 10 UAPF flaps. Standardized assessment of outcomes was performed, including duration of operation, objective sensory recovery, cold intolerance, time of returning to work, active total range of motion (ROM) of the injured fingers, and the cosmetic appearance of the donor/recipient sites. Results All flaps survived completely, and the follow-up duration was 13.5 months. The mean duration of the complete surgical procedure for AVFs was distinctly shorter than that of the other flaps (p<0.05). AVFs were employed to reconstruct skin defects and extensor tendon defects using a vascularized palmaris longus graft in 4 fingers. Digital blood supply was reestablished in 4 fingers by flow-through technique when using AVFs. Optimal sensory recovery was better with AVFs and SPBRA flaps as compared with UAPF flaps and PIPFs (p<0.05). No significant differences were noted in ROM or cold intolerance between the 4 groups. Optimal cosmetic satisfaction was noted for the recipient sites of AVFs and the donor sites of SPBRA flaps. The number of second-stage defatting operations required for AVFs was considerably lesser than that for the other flaps. Conclusion All 4 types of free flaps from the ipsilateral extremity are a practical choice in finger reconstruction for small/moderate-sized skin defects. AVFs play an important role in such operations due to the wider indications, and better sensory recovery and cosmetic appearance associated with this method.